Polyurethane material as well as preparation method and application thereof
By using components such as 1,5-pentadiisocyanate and oligomeric polyol in 3D printed polyurethane materials, controlling their component ratios, the problems of insufficient mechanical properties and high melting point of existing materials are solved, and the low material is achieved Melting point, good elasticity and yellowing resistance, suitable for 3D printing.
Patent Information
- Application Number
- CN202411741540.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
The existing 3D printed polyurethane materials have insufficient mechanical properties, high melting point and prone to yellowing, which limits their application in the field of low processing temperatures.
Using 1,5-pentadiisocyanate, oligomer polyol, chain extender, antioxidant, anti-hydrolytic agent, lubricant and catalyst compounding, control the 1,5-pentadiisocyanate and chain extender in polyurethane materials. The total mass accounts for between 35% and 45%.
The prepared polyurethane material has the characteristics of low melting point, good elasticity, low haze, resistance to yellowing, tensile strength and high elongation of break, and is suitable for 3D printing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials, and in particular relates to a polyurethane material and a preparation method and application thereof. Background Art
[0002] With the continuous development of additive manufacturing technology, 3D printing has been widely used in industries such as biology, medicine, electronics, construction, and handmade manufacturing. Compared with traditional manufacturing methods such as extrusion molding and compression molding, 3D printing technology can not only quickly mold complex and fine products, but also select different materials for rapid manufacturing according to different functions and performance requirements. With this advantage, 3D printing has received more and more attention, and more and more 3D printed products have been applied to people's lives, studies, and work. Among the common 3D printing technologies, FDM technology has the advantages of simple manufacturing and low cost. The molding material is mainly wire, and the commonly used wire is mainly made of high-brittleness PLA, high-hardness ABS or high-elasticity TPU materials.
[0003] CN105418874A discloses a 3D printing thermoplastic polyurethane material and a preparation method thereof. The components of the 3D printing thermoplastic polyurethane material are as follows, by weight: 35-75 parts of macromolecular polyol, 0-10 parts of fluorine-containing polyol, 2-25 parts of small molecule chain extender, 0-7 parts of fluorine-containing chain extender, 5-60 parts of isocyanate, 0-8 parts of hydrolysis stabilizer, and 0-10 parts of other additives. The 3D printing thermoplastic polyurethane material provided by the technical solution has excellent thermal stability, low shrinkage, high mechanical properties, and low water absorption, but the mechanical properties still need to be improved.
[0004] In addition, the high-elasticity TPU material requires high processing temperature due to its high melting point, is prone to yellowing and other problems, and limits its possibility of use in some areas with lower processing temperatures.
[0005] CN1 06893306A discloses a low-melting-point polyurethane 3D printing material and a preparation method thereof. The low-melting-point polyurethane 3D printing material adopts the following components and raw material ratios, wherein the raw material parts are all molar parts unless otherwise specified; 80-150 parts of polyol containing furan ring, 80-120 parts of diisocyanate, 1-20 parts of diisocyanate composition with maleimide as terminal group, and 0.1-5 parts of dendritic polymer, wherein the molar part of polyol containing furan ring / the molar part of diisocyanate is ≥1. The low-melting-point polyurethane 3D printing material provided by this technical solution has a low melting temperature and high tensile strength, but low elongation at break and poor toughness.
[0006] Therefore, it is necessary to develop a polyurethane material that can be used for 3D printing with good mechanical properties, low melting point, and resistance to yellowing. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a polyurethane material and a preparation method and application thereof. The polyurethane material has the characteristics of low melting point, good elasticity, low haze, yellowing resistance, high tensile strength and elongation at break.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a polyurethane material, wherein the raw materials for preparing the polyurethane material include the following components: 1,5-pentanediisocyanate (PDI), oligomer polyol, chain extender, antioxidant, anti-hydrolysis agent, lubricant and catalyst;
[0010] Taking the total mass of the raw materials for preparing the polyurethane material as 100%, the total mass of 1,5-pentanediisocyanate and the chain extender accounts for 35% to 45%, for example, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45% or any value within the range between any two of the above values.
[0011] In the present invention, the isocyanate is 1,5-pentanediisocyanate. Since it has a straight-chain configuration and an odd number of carbon atoms, the obtained polyurethane material has good yellowing resistance and high flexibility.
[0012] In the present invention, isocyanate and chain extender participate in the reaction to form a hard segment in the polyurethane material, and the total mass of the isocyanate and chain extender is recorded as HS based on the total mass of the raw materials for preparing the polyurethane material as 100%; based on the total mass of the raw materials for preparing the polyurethane material as 100%, the total mass of 1,5-pentane diisocyanate and chain extender needs to be accurately controlled to be in the range of 35% to 45%, and the 1,5-pentane diisocyanate and chain extender participate in the reaction to form a hard segment in the polyurethane material. The inventor found that if the total mass of 1,5-pentane diisocyanate and chain extender is less than 35%, the melting point of the prepared polyurethane material is low, but the haze is high, the transparency is poor, the elasticity is low, and the mechanical properties are poor, so the melt strength is poor, the extruded filaments are easy to break and there are many surface defects; if the total mass of 1,5-pentane diisocyanate and chain extender is greater than 45%, the hardness of the prepared polyurethane material is high, and the tensile strength, elongation and elasticity are poor, which leads to excessive rigidity of the extruded filaments, too high melting point, low strength and low elasticity.
[0013] Preferably, the raw materials for preparing the polyurethane material include the following components in parts by mass: 24 to 33 parts of 1,5-pentanediisocyanate (for example, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts or any value within a range between any two of the above values), 52 to 65 parts of oligomer polyol (for example, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 65 parts or any value within a range between any two of the above values), 11 to 14 parts of chain extender (for example, 11 parts, 11.3 parts, 11.6 parts, 11.9 parts, 12.2 parts, 12.5 parts, 12.8 parts, 13.1 parts, 13.4 parts or 13.7 parts, 14 parts or any value within a range between any two of the above values), and 0.4 to 0.05 parts of antioxidant. 0.6 parts (e.g. 0.4 parts, 0.42 parts, 0.44 parts, 0.46 parts, 0.48 parts, 0.50 parts, 0.52 parts, 0.54 parts, 0.56 parts, 0.58 parts, 0.6 parts or any values in the range between any two of the above values), 0.5-1 parts (e.g. 0.5 parts, 0.55 parts, 0.60 parts, 0.65 parts, 0.70 parts, 0.75 parts, 0.80 parts, 0.85 parts, 0.90 parts, 0.95 parts, 1 part or any values in the range between any two of the above values) of anti-hydrolysis agent and 0.5-1 parts (e.g. 0.5 parts, 0.55 parts, 0.60 parts, 0.65 parts, 0.70 parts, 0.75 parts, 0.80 parts, 0.85 parts, 0.90 parts, 0.95 parts, 1 part or any values in the range between any two of the above values) of lubricant.
[0014] Preferably, the mass content of the catalyst in the raw materials for preparing the polyurethane material is 200-400 ppm, for example, 220 ppm, 240 ppm, 260 ppm, 280 ppm, 300 ppm, 320 ppm, 340 ppm, 360 ppm or 380 ppm.
[0015] Preferably, the molar ratio of -NCO groups to -OH groups in the raw materials for preparing the polyurethane material is 1 to 1.05, for example, 1, 1.005, 1.01, 1.015, 1.02, 1.025, 1.03, 1.035, 1.04, 1.045, 1.05 or any value in the range between any two of the above values.
[0016] In the present invention, the molar ratio of -NCO groups to -OH groups in the raw materials for preparing the polyurethane material is recorded as R value, which is preferably precisely controlled in the range of 1 to 1.05. The inventors have found that if the R value is <1, a polyurethane material terminated with a hydroxyl group is formed, which has a low molecular weight and relatively poor mechanical properties. If the R value is >1.05, a polyurethane material terminated with an isocyanate group is formed, and side reactions are prone to occur, resulting in poor mechanical properties and reduced elasticity.
[0017] Preferably, the 1,5-pentane diisocyanate is bio-based 1,5-pentane diisocyanate.
[0018] In the present invention, the 1,5-pentane diisocyanate is preferably bio-based 1,5-pentane diisocyanate. The use of bio-based 1,5-pentane diisocyanate can not only achieve green raw material sources and resource conservation, but also ensure that the prepared polyurethane material is environmentally friendly and healthy, and is suitable for high-end applications.
[0019] Preferably, the mass percentage content of bio-based carbon in the bio-based 1,5-pentanediisocyanate is 60% to 71.4%, for example, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71.4% or any value in the range between any two of the above values.
[0020] Preferably, the hydrolyzed chlorine content of the bio-based 1,5-pentanediisocyanate is ≤60 mg / kg (e.g., 10 mg / kg, 15 mg / kg, 20 mg / kg, 25 mg / kg, 30 mg / kg, 35 mg / kg, 40 mg / kg or 45 mg / kg, etc.).
[0021] Preferably, the solid content of the bio-based 1,5-pentanediisocyanate is 100%.
[0022] In the present invention, the hydrolyzed chlorine content of the bio-based 1,5-pentanediisocyanate is preferably ≤60 mg / kg. If the hydrolyzed chlorine content is too high, the prepared polyurethane material will have high haze and be prone to yellowing.
[0023] Preferably, the weight average molecular weight of the oligomer polyol is 1000-2000 (eg, 1000, 1400, 1800, 2000 or any value within the range between any two of the above values), more preferably 1000 or 2000.
[0024] Preferably, the oligomer polyol comprises polyester polyol and / or polyether polyol.
[0025] Preferably, the polyester polyol includes any one of polybutylene adipate diol (PBA), polypropylene sebacate diol or polybutylene sebacate diol (PBS) or a combination of at least two thereof, and more preferably polybutylene adipate diol.
[0026] Preferably, the polyether polyol includes polytrimethylene ether glycol and / or polytetramethylene ether glycol, and more preferably polytetramethylene ether glycol.
[0027] Preferably, the polytrimethylene ether glycol comprises bio-based polytrimethylene ether glycol.
[0028] Preferably, the polypropylene sebacate diol comprises bio-based polypropylene sebacate diol.
[0029] Preferably, the chain extender includes any one of 1,4-butanediol, 1,3-propylene glycol or 1,6-hexanediol or a combination of at least two thereof, and is further preferably 1,4-butanediol and / or 1,3-propylene glycol.
[0030] Preferably, the antioxidant includes hindered phenol antioxidants and phosphite antioxidants.
[0031] Preferably, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:(1-2), such as 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or any ratio within the range between any two of the above ratios.
[0032] Preferably, the hindered phenol antioxidant includes any one of antioxidant 1010, antioxidant 1076 or antioxidant 501, or a combination of at least two of them, and antioxidant 501 is more preferably.
[0033] Preferably, the phosphite antioxidant includes antioxidant 168 and / or antioxidant 626, and more preferably antioxidant 168.
[0034] Preferably, the anti-hydrolysis agent is a monomeric carbodiimide anti-hydrolysis agent.
[0035] Preferably, the monomeric carbodiimide anti-hydrolysis agent includes HyMax 1010 from Langyi New Materials.
[0036] Preferably, the lubricant includes any one of montan wax, polyethylene wax or special ester wax, or a combination of at least two of them, and more preferably special ester wax.
[0037] Preferably, the special ester wax includes Honeywell's special ester wax HPL-6901.
[0038] Preferably, the catalyst comprises an organotin catalyst.
[0039] Preferably, the organotin catalyst includes organotin catalyst T9 and / or organotin catalyst T12, and more preferably organotin catalyst T12.
[0040] In a second aspect, the present invention provides a method for preparing the polyurethane material as described in the first aspect, the preparation method comprising the following steps:
[0041] (1) mixing an oligomer polyol, a portion of 1,5-pentanediisocyanate, an antioxidant and an anti-hydrolysis agent, and reacting them to obtain a prepolymer;
[0042] (2) mixing the prepolymer obtained in step (1), a chain extender and a lubricant, and reacting them to obtain an intermediate product;
[0043] (3) The intermediate product obtained in step (2), the remaining 1,5-pentanediisocyanate and the catalyst are mixed, heat treated, and aged to obtain the polyurethane material.
[0044] Preferably, the mixing in step (2) is performed by adding a chain extender and a lubricant to the prepolymer obtained in step (1) for mixing.
[0045] Preferably, the mixing in step (3) is to add the remaining 1,5-pentanediisocyanate and the catalyst to the intermediate product obtained in step (2) and mix them.
[0046] Preferably, the mass ratio of the portion of 1,5-pentane diisocyanate in step (1) to the remaining 1,5-pentane diisocyanate in step (3) is (0.6-2):1, for example, 0.6:1, 0.8:1, 1.0:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1 or any ratio within the range between any two of the above ratios.
[0047] Preferably, the oligomer polyol in step (1) is -0.1 to -0.06 MPa (e.g., -0.1 MPa, -0.09 MPa, -0.08 MPa, -0.07 MPa, -0.06 MPa or any value within the range of any two values above), 105 to 120° C. (e.g., 105° C., 106° C., 107° C., 108° C., 109° C., 110° C., 111° C., 112° C. The method is obtained by pre-treating the mixture under vacuum for 1 to 2 h (e.g., 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2 h or any value in the range between any two of the above values) and removing water under vacuum for 1 to 2 h (e.g., 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2 h or any value in the range between any two of the above values).
[0048] Preferably, the reaction in step (1) comprises reacting at 65-75°C (e.g., 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C or any value in the range between any two of the above values) for 25-35 min (e.g., 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min or any value in the range between any two of the above values). any value in the range between the above), and then react at 80-85°C (e.g., 80°C, 80.5°C, 81°C, 81.5°C, 82°C, 82.5°C, 83°C, 83.5°C, 84°C, 84.5°C, 85°C or any value in the range between any two of the above values) for further 2-3h (e.g., 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h or any value in the range between any two of the above values).
[0049] Preferably, the reaction temperature in step (2) is 70-80°C (e.g., 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C or any value in the range between any two of the above values), and the reaction time is 0.5-1.5h (e.g., 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h or any value in the range between any two of the above values).
[0050] Preferably, the mixing in step (3) is performed by stirring and mixing under a vacuum condition of -0.06 to -0.08 MPa (for example, -0.06 MPa, -0.062 MPa, -0.064 MPa, -0.066 MPa, -0.068 MPa, -0.070 MPa, -0.072 MPa, -0.074 MPa, -0.076 MPa, -0.078 MPa, -0.08 MPa or any value in the range between any two of the above values) for 30 to 60 s (for example, 30 s, 35 s, 40 s, 45 s, 50 s, 55 s, 60 s or any value in the range between any two of the above values), and the stirring speed is 1500 to 2000 rpm (for example, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm or any value in the range between any two of the above values).
[0051] Preferably, the temperature of the heat treatment in step (3) is 115-125°C (for example, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C, 121°C, 122°C, 123°C, 124°C, 125°C or any value in the range between any two of the above values), and the time is 1.5-2h (for example, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h or any value in the range between any two of the above values).
[0052] Preferably, the aging temperature in step (3) is 95-105°C (for example, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, 101°C, 102°C, 103°C, 104°C, 105°C or any value in the range between any two of the above values), and the time is 15-20h (for example, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, 20h or any value in the range between any two of the above values).
[0053] In a third aspect, the present invention provides a use of the polyurethane material as described in the first aspect in 3D printing.
[0054] Preferably, the application specifically comprises the following steps:
[0055] (a) The polyurethane material is crushed, dried, and extruded using a single-screw extruder to obtain a TPU wire harness.
[0056] (b) The TPU wire harness is loaded into the 3D printer, and the 3D model is designed using 3D design software. The 3D printed product is obtained by printing under the set printing temperature and wire feed speed conditions.
[0057] Preferably, the pulverization in step (a) is performed by placing the mixture at room temperature for 3 to 5 days before pulverization.
[0058] Preferably, the room temperature is 20-30°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C or any value in the range between any two of the above values.
[0059] Preferably, the pulverization in step (a) is pulverization to a particle size of ≤5 mm, such as 1 mm, 2 mm, 3 mm, 4 mm, 5 mm or any value within the range between any two of the above values.
[0060] Preferably, the drying in step (a) comprises drying at -1 to 0 MPa (e.g., -1 MPa, -0.9 MPa, -0.8 MPa, -0.7 MPa, -0.6 MPa, -0.5 MPa, -0.4 MPa, -0.3 MPa, -0.2 MPa, -0.1 MPa, 0 MPa). a or any value in the range between any two of the above values), dried in a vacuum oven at 55-65°C (55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C or any value in the range between any two of the above values) for 8-10h (for example, 8h, 8.2h, 8.4h, 8.6h, 8.8h, 9.0h, 9.2h, 9.4h, 9.6h, 9.8h, 10h or any value in the range between any two of the above values).
[0061] Preferably, the aspect ratio of the single screw extruder is 11-13, more preferably 12.
[0062] Preferably, the temperature of one section of the single screw extruder is 70°C, 155-180°C (e.g., 155°C, 158°C, 161°C, 164°C, 167°C, 170°C, 173°C, 176°C, 179°C, 180°C or any value within the range between any two of the above values), 130-140°C (e.g., 130°C, 131°C, 132°C, 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C, 140°C or any value within the range between any two of the above values), The screw speed is 130-140°C (for example, 130°C, 131°C, 132°C, 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C, 140°C or any value in the range between any two of the above values), and the screw speed is 12-20r / min (for example, 12r / min, 13r / min, 14r / min, 15r / min, 16r / min, 17r / min, 18r / min, 19r / min, 20r / min or any value in the range between any two of the above values).
[0063] Preferably, the diameter of the TPU harness is 1.75±0.05 mm (e.g. 1.70 mm , 1.71 mm , 1.72mm, 1.73mm, 1.74mm, 1.75mm, 1.76mm, 1.77mm, 1.78mm, 1.79mm, 1.80mm or any value in the range between any two of the above values).
[0064] Preferably, the 3D printer is an FDM 3D printer.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] The invention is compounded by 1,5-pentane diisocyanate, oligomer polyol, chain extender, antioxidant, anti-hydrolysis agent, lubricant and catalyst, wherein the total mass of 1,5-pentane diisocyanate and chain extender is controlled at 35% to 45% based on the total mass of polyurethane material as 100%, so that the prepared polyurethane material has the characteristics of low melting point, good elasticity, low haze, yellowing resistance, high tensile strength and elongation at break. The polyurethane material can achieve a rebound rate of 58% to 68%, a tensile strength of 29.2 to 40.2 MPa, an elongation at break of 625% to 886.9%, a melting point of 112 to 152°C, a haze of 9% to 15%, and a yellowing degree of 0. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] Some of the raw materials for the following examples and comparative examples are as follows:
[0069] Bio-based 1,5-pentanediisocyanate, wherein the mass percentage content of bio-based carbon is 71.4%, the hydrolyzed chlorine content is 60 mg / kg, and the solid content is 100%.
[0070] Example 1
[0071] The present embodiment provides a polyurethane material and a preparation method and application thereof, wherein the raw materials for preparing the polyurethane material include the following components by mass: 28 parts of 1,5-pentanediisocyanate (bio-based 1,5-pentanediisocyanate), 59 parts of oligomer polyol (polybutylene adipate diol, weight average molecular weight of 1000), 11 parts of chain extender (1,4-butanediol), 0.4 parts of antioxidant (antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1), 0.6 parts of anti-hydrolysis agent (Langyi New Materials HyMax1010), 1 part of lubricant (Honeywell's special ester wax HPL-6901) and catalyst, and the mass content of the catalyst (organic tin catalyst T12) in the raw materials for preparing the polyurethane material is 200ppm. The brand of the above-mentioned polybutylene adipate diol is HDPOL-4420T, and the manufacturer is Shanghai Huide Technology Co., Ltd.
[0072] The preparation method comprises the following steps:
[0073] (1) The oligomer polyol was dehydrated under vacuum at -0.1 MPa and 120° C. for 1.5 h, cooled to 70° C., 18.2 parts by mass of 1,5-pentanediisocyanate, an antioxidant and an anti-hydrolysis agent were added and mixed, reacted for 30 min, and then heated to 85° C. and reacted for another 2.5 h to obtain a prepolymer.
[0074] (2) Add a chain extender and a lubricant to the prepolymer prepared in step (1), mix them, and react them at 85° C. for 1 hour to obtain an intermediate product.
[0075] (3) Add the remaining 9.8 parts by mass of 1,5-pentanediisocyanate and the catalyst to the intermediate product obtained in step (2), stir at high speed (2000 rpm) for 45 seconds under a vacuum condition of -0.08 MPa, pour out and form, heat treat at 120°C for 2 hours, and then mature at 100°C for 17 hours to obtain the polyurethane material.
[0076] The application comprises the following steps:
[0077] (a) The polyurethane material was placed for 3 days and then crushed to an average particle size of 5 mm. The material was placed in a vacuum oven at -0.1 MPa and 60°C for drying for 8 h. The material was extruded using a single screw extruder with a length-to-diameter ratio of 12. The temperatures of each section of the single screw extruder were 70°C, 180°C, 158°C, and 155°C. The screw speed was 15 r / min. The material was then water-cooled and wound on a winding machine to produce a TPU wire harness with a diameter of 1.75±0.05 mm.
[0078] (b) The TPU wiring harness obtained in step (a) is loaded into a 3D printer, a 3D model is designed using 3D design software, and printing is performed at a set printing temperature of 178° C. and a wire feed speed of 30 mm / s to obtain a 3D printed product.
[0079] Example 2
[0080] This embodiment provides a polyurethane material and its preparation method and application. The difference between the embodiment 1 and the embodiment 1 is that the raw materials for preparing the polyurethane material include the following components by mass: 32 parts of 1,5-pentanediisocyanate (bio-based 1,5-pentanediisocyanate), 53 parts of oligomer polyol (polytetramethylene ether glycol, weight average molecular weight of 1000), 13 parts of chain extender (1,4-butanediol), 0.4 parts of antioxidant (antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1), 0.6 parts of anti-hydrolysis agent (Langyi New Materials HyMax 1010), 1 part of lubricant (Honeywell's special ester wax HPL-6901) and catalyst, and the mass content of catalyst (organic tin catalyst T12) in the raw materials for preparing the polyurethane material is 200ppm. The brand of the above-mentioned polytetramethylene ether glycol is PTMEG-1000, and the manufacturer is Hyosung Chemical Co., Ltd.
[0081] In the preparation method, the mass fraction of 1,5-pentane diisocyanate in step (1) is adjusted to 16.7 parts; and the mass fraction of 1,5-pentane diisocyanate in step (3) is adjusted to 15.3 parts.
[0082] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 160° C., 130° C., and 130° C.; and the printing temperature in step (b) is adjusted to 165° C.
[0083] Other conditions are the same as in Example 1.
[0084] Example 3
[0085] The present embodiment provides a polyurethane material, a preparation method and an application thereof. The difference between the present embodiment and the embodiment 1 is that the raw materials for preparing the polyurethane material include the following components in parts by mass: 25 parts of 1,5-pentanediisocyanate (bio-based 1,5-pentanediisocyanate), 63 parts of oligomer polyol (bio-based polytrimethylene ether glycol, weight-average molecular weight of 2000), 10 parts of chain extender (1,3-propylene glycol), 0.4 parts of antioxidant (antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1), 0.6 parts of anti-hydrolysis agent (Langyi New Materials HyMax1010), 1 part of lubricant (Honeywell's special ester wax HPL-6901) and a catalyst. The mass content of the catalyst (organic tin catalyst T12) in the raw materials for preparing the polyurethane material is 200 ppm.
[0086] The brand of the above-mentioned bio-based polytrimethylene ether glycol is H2000, the manufacturer is SK Chemical, and the mass percentage content of bio-based carbon is 100%.
[0087] In the preparation method, the mass fraction of 1,5-pentane diisocyanate in step (1) is adjusted to 9.7 parts; and the mass fraction of 1,5-pentane diisocyanate in step (3) is adjusted to 15.3 parts.
[0088] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 190° C., 155° C., and 155° C.; and the printing temperature in step (b) is adjusted to 190° C.
[0089] Other conditions are the same as in Example 1.
[0090] Example 4
[0091] The present embodiment provides a polyurethane material, a preparation method and an application thereof. The difference between the present embodiment and the embodiment 1 is that the raw materials for preparing the polyurethane material include the following components in parts by mass: 30 parts of 1,5-pentanediisocyanate (bio-based 1,5-pentanediisocyanate), 58 parts of oligomer polyol (bio-based polypropylene sebacate diol and bio-based polytrimethylene ether glycol in a mass ratio of 46.4:11.6), 10 parts of chain extender (1,3-propylene glycol), 0.4 parts of antioxidant (antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1), 0.6 parts of anti-hydrolysis agent (Langyi New Materials HyMax 1010), 1 part of lubricant (Honeywell's special ester wax HPL-6901) and a catalyst. The mass content of the catalyst (organic tin catalyst T12) in the raw materials for preparing the polyurethane material is 350 ppm.
[0092] The weight average molecular weight of the above-mentioned bio-based polypropylene sebacate diol is 1000, the brand is PL6310B, the manufacturer is Dongguan Hongshi Functional Materials Technology Co., Ltd., and the mass percentage content of bio-based carbon is 100%;
[0093] The weight average molecular weight of the above-mentioned bio-based polytrimethylene ether glycol is 1000, the brand is H1000, the manufacturer is SK Chemical, and the mass percentage content of bio-based carbon is 100%.
[0094] In the preparation method, the mass fraction of 1,5-pentane diisocyanate in step (1) is adjusted to 18.1 parts; and the mass fraction of 1,5-pentane diisocyanate in step (3) is adjusted to 11.9 parts.
[0095] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 168° C., 140° C., and 140° C.; and the printing temperature in step (b) is adjusted to 175° C.
[0096] Other conditions are the same as in Example 1.
[0097] Example 5
[0098] This embodiment provides a polyurethane material, a preparation method and an application thereof. The difference between this embodiment and Example 1 is that the mass fraction of the antioxidant (antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) is adjusted to 0.6 parts, the mass fraction of the anti-hydrolysis agent (Langyi New Materials HyMax 1010) is adjusted to 0.9 parts, and the mass fraction of the lubricant (Honeywell's special ester wax HPL-6901) is adjusted to 0.5 parts.
[0099] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 180° C., 158° C., and 155° C.; and the printing temperature in step (b) is adjusted to 180° C.
[0100] Other conditions are the same as in Example 1.
[0101] Example 6
[0102] This embodiment provides a polyurethane material, a preparation method and an application thereof, which differs from Embodiment 1 in that polybutylene adipate diol (weight average molecular weight of 1000) is replaced with the same mass of bio-based polypropylene sebacate diol (weight average molecular weight of 1000).
[0103] The weight average molecular weight of the above-mentioned bio-based polypropylene sebacate diol is 1000, the brand is PL6310B, the manufacturer is Dongguan Hongshi Functional Materials Technology Co., Ltd., and the mass percentage content of bio-based carbon is 100%;
[0104] In the application, the temperatures of each section of the single-screw extruder in step (a) are adjusted to 70° C., 182° C., 160° C., and 160° C.; and the printing temperature in step (b) is adjusted to 183° C.
[0105] Other conditions are the same as in Example 1.
[0106] Example 7
[0107] This embodiment provides a polyurethane material, a preparation method and an application thereof, which differs from Embodiment 2 in that polytetramethylene ether glycol (weight average molecular weight is 1000) is replaced with bio-based polytrimethylene ether glycol (weight average molecular weight is 1000) of the same mass.
[0108] The weight average molecular weight of the above-mentioned bio-based polytrimethylene ether glycol is 1000, the brand is H1000, the manufacturer is SK Chemical, and the mass percentage content of bio-based carbon is 100%.
[0109] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 163° C., 140° C., and 140° C.; and the printing temperature in step (b) is adjusted to 163° C.
[0110] Other conditions are the same as those in Example 2.
[0111] Example 8
[0112] This embodiment provides a polyurethane material and a preparation method and application thereof. The difference between this embodiment and Embodiment 1 is that the organotin catalyst T12 is replaced with an organotin catalyst T9 of the same mass.
[0113] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 180° C., 158° C., and 156° C.; and the printing temperature in step (b) is adjusted to 180° C.
[0114] Other conditions are the same as in Example 1.
[0115] Comparative Example 1
[0116] This comparative example provides a polyurethane material and a preparation method and application thereof, which differs from Example 1 only in that 28 parts by mass of 1,5-pentamethylene diisocyanate (bio-based 1,5-pentamethylene diisocyanate) is replaced with 32.6 parts by mass of diphenylmethane diisocyanate (MDI), and the mass fraction of the chain extender (1,4-butanediol) is adjusted to 6.4 parts, so that the hard segment content in the polyurethane material is the same as that in Example 1;
[0117] In the preparation method, the mass fraction of diphenylmethane diisocyanate in step (1) is adjusted to 29.5 parts; the mass fraction of diphenylmethane diisocyanate in step (3) is adjusted to 3.1 parts.
[0118] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 215° C., 185° C., and 185° C.; and the printing temperature in step (b) is adjusted to 215° C.
[0119] Other conditions are the same as in Example 1.
[0120] Comparative Example 2
[0121] This comparative example provides a polyurethane material and a preparation method and application thereof, which differs from Example 1 only in that 28.8 parts by mass of 1,5-pentamethylene diisocyanate (bio-based 1,5-pentamethylene diisocyanate) is replaced with 28.6 parts by mass of 1,6-hexamethylene diisocyanate (HDI), and the mass fraction of the chain extender (1,4-butanediol) is adjusted to 10.2 parts; the hard segment content in the polyurethane material is the same as that in Example 1;
[0122] In the preparation method, the mass fraction of 1,6-hexamethylene diisocyanate in step (1) is adjusted to 19.8 parts; and the mass fraction of 1,6-hexamethylene diisocyanate in step (3) is adjusted to 9 parts.
[0123] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 210° C., 170° C., and 170° C.; and the printing temperature in step (b) is adjusted to 212° C.
[0124] Other conditions are the same as in Example 1.
[0125] Comparative Example 3
[0126] This comparative example provides a polyurethane material and a preparation method and application thereof, which differs from Example 1 only in that the mass fraction of 1,5-pentamethylene diisocyanate (bio-based 1,5-pentamethylene diisocyanate) is adjusted to 24.5 parts, the mass fraction of oligomer polyol (polybutylene adipate diol, weight average molecular weight of 1000) is adjusted to 65.5 parts, and the mass fraction of chain extender (1,4-butanediol) is adjusted to 8 parts;
[0127] In the preparation method, the mass fraction of 1,5-pentane diisocyanate in step (1) is adjusted to 18.4 parts; and the mass fraction of 1,5-pentane diisocyanate in step (3) is adjusted to 6.1 parts.
[0128] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 150° C., 140° C., and 140° C.; and the printing temperature in step (b) is adjusted to 150° C.
[0129] Other conditions are the same as in Example 1.
[0130] Comparative Example 4
[0131] This comparative example provides a polyurethane material and a preparation method and application thereof, which differs from Example 1 only in that the mass fraction of 1,5-pentamethylene diisocyanate (bio-based 1,5-pentamethylene diisocyanate) is adjusted to 32 parts, the mass fraction of oligomer polyol (polybutylene adipate diol, weight average molecular weight of 1000) is adjusted to 52 parts, and the mass fraction of chain extender (1,4-butanediol) is adjusted to 14 parts;
[0132] In the preparation method, the mass fraction of 1,5-pentane diisocyanate in step (1) is adjusted to 18.2 parts; and the mass fraction of 1,5-pentane diisocyanate in step (3) is adjusted to 13.8 parts.
[0133] In the application, the temperatures of the various sections of the single-screw extruder in step (a) are adjusted to 70° C., 200° C., 165° C., and 160° C.; and the printing temperature in step (b) is adjusted to 200° C.
[0134] Other conditions are the same as in Example 1.
[0135] Comparative Example 5
[0136] This comparative example provides a polyurethane material and a preparation method and application thereof. The only difference between the comparative example and Example 1 is that the preparation method is adjusted to the following steps: dehydrating the oligomer polyol under vacuum at -0.1 MPa and 120°C for 1.5 hours, cooling to 70°C, adding a chain extender, an antioxidant, an anti-hydrolysis agent and a lubricant and mixing, then adding 1,5-pentanediisocyanate and a catalyst at one time and mixing, and then adding to a twin-screw extruder at 180°C for extrusion, heat-treating the extrudate at 120°C for 2 hours and then maturing at 100°C for 17 hours to obtain the polyurethane material.
[0137] In the application, the temperatures of the various sections of the single screw extruder in step (a) are adjusted to 70° C., 185° C., 160° C., and 160° C., and the printing temperature in step (b) is adjusted to 185° C.
[0138] The polyurethane materials provided in Examples 1-8 and Comparative Examples 1-5 were tested as follows.
[0139] (1) Rebound rate: The resilience of a cylinder made of polyurethane material was tested according to ASTM-D2632. The diameter of the cylinder was 28 mm and the thickness was 12.5 mm.
[0140] (2) Tensile strength and elongation at break: The mechanical properties of type 1 dumbbell-shaped polyurethane material samples were tested according to ASTM-D412 standard;
[0141] (3) Melting point: The thermal performance parameters of a 10 mg polyurethane material sample were tested by DSC, and the heating and cooling rate of the equipment was 10 °C / m i n ;
[0142] (4) Haze: According to GB / T 2410-2008, the haze of a polyurethane material sample with a diameter of 50 mm and a thickness of 2 mm was tested. The formula H = (T 4 / T 2 -T 3 / T 1 )×100 to calculate the haze of polyurethane materials;
[0143] (5) Yellowing grade: The polyurethane material samples were subjected to a 7-day weathering test according to the typical test condition 2 of the fluorescent ultraviolet lamp exposure test in GB / T 14522-2008, and then the yellowness was calculated according to the ASTM E313 standard using the D65 / 10 degree. The formula is as follows: Yi = 100 (1.3013 × X - 1.1498 × Z) / Y; Yellowness index change ΔY i =Y i -Y i0 , Y i Y is the yellow index after the test, i0 is the yellow index before the test; ΔY i The yellowing index is the yellowing grade, and the yellowing grades are divided as follows:
[0144] Level 0: no discoloration, ΔYi≤1.5;
[0145] Level 1: Very slight discoloration, 1.6<ΔYi≤3.0;
[0146] Level 2: Slight discoloration, 3.1<ΔYi≤6.0;
[0147] Level 3: obvious discoloration, 6.1<ΔYi≤9.0;
[0148] Level 4: significant discoloration, 9.1<ΔYi≤12.0;
[0149] Level 5: Severe discoloration, 12.0<ΔYi.
[0150] The test results are shown in Table 1 and Table 2.
[0151] Table 1
[0152]
[0153] Table 2
[0154]
[0155]
[0156] In Table 2, “ / ” means that the data for this item is not available.
[0157] As shown in Table 1 and Table 2, the polyurethane material provided in Examples 1-8 has a rebound rate of 58% to 68%, a tensile strength of 29.2 to 40.2 MPa, an elongation at break of 625% to 886.9%, a melting point of 112 to 152°C, a haze of 9% to 15%, and a yellowing level of 0.
[0158] Compared with Example 1, if polybutylene adipate diol is replaced with polypropylene sebacate diol of the same mass (Example 6), the resilience of the polyurethane material will decrease, and the melting point and haze will increase. It can be seen that the polyurethane material prepared by preferably using polybutylene adipate diol as the oligomer polyol has better performance.
[0159] Compared with Example 2, if polytetramethylene ether glycol is replaced with polytrimethylene ether glycol of the same mass (Example 7), the tensile strength of the polyurethane material will decrease. It can be seen that the polyurethane material prepared by preferably using polytetramethylene ether glycol as the oligomer polyol has better performance.
[0160] Compared with Example 1, if 1,5-pentane diisocyanate is replaced by diphenylmethane diisocyanate (Comparative Example 1), the R value and the hard segment content (HS) are kept unchanged. Diphenylmethane diisocyanate is easily oxidized and discolored due to containing a large number of benzene rings, which makes the polyurethane material easily turn yellow when heated and exposed to light and has deviations in mechanical properties.
[0161] Compared with Example 1, if 1,5-pentanediisocyanate is replaced by 1,6-hexamethylenediisocyanate (Comparative Example 2), while keeping the R value and the hard segment content (HS) unchanged, 1,6-hexamethylenediisocyanate has a high symmetry and a more regular structure, which increases the crystallinity inside the polyurethane material, resulting in the adverse effects of increased haze and melting point.
[0162] Compared with Example 1, if the total mass of 1,5-pentane diisocyanate and the chain extender is too low (Comparative Example 3) based on the total mass of the polyurethane material, the prepared polyurethane material has a low melting point, but high haze, poor transparency, low elasticity, and poor mechanical properties, resulting in poor melt strength, easy breakage of the extruded filaments, and more surface defects; if the total mass of 1,5-pentane diisocyanate and the chain extender is too high (Comparative Example 4) based on the total mass of the polyurethane material, the hardness of the prepared polyurethane material is high, and the tensile strength, elongation at break, and elasticity deteriorate, resulting in excessive rigidity of the extruded filaments, too high melting point, and low strength and low elasticity.
[0163] Compared with Example 1, the polyurethane material prepared by the preparation method of Comparative Example 5 has high haze, poor transparency, low elasticity, poor mechanical properties and high melting point. The reason is that the one-step process of twin-screw polymerization will bring about an irregular molecular chain structure and more side reactions, which will deteriorate the performance of the polyurethane material.
[0164] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a polyurethane material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyurethane material, characterized in that: The raw materials for preparing the polyurethane material include the following components: 1,5-pentanediisocyanate, oligomer polyol, chain extender, antioxidant, anti-hydrolysis agent, lubricant and catalyst; Taking the total mass of the raw materials for preparing the polyurethane material as 100%, the total mass of 1,5-pentanediisocyanate and the chain extender accounts for 35% to 45%.
2. The polyurethane material according to claim 1, characterized in that: The raw materials for preparing the polyurethane material include the following components by mass: 24-33 parts of 1,5-pentanediisocyanate, 52-65 parts of oligomer polyol, 11-14 parts of chain extender, 0.4-0.6 parts of antioxidant, 0.5-1 parts of anti-hydrolysis agent and 0.5-1 parts of lubricant; Preferably, the mass content of the catalyst in the raw materials for preparing the polyurethane material is 200 to 400 ppm.
3. The polyurethane material according to claim 1 or 2, characterized in that: The molar ratio of -NCO groups to -OH groups in the raw materials for preparing the polyurethane material is 1 to 1.
05.
4. The polyurethane material according to any one of claims 1 to 3, characterized in that: The 1,5-pentane diisocyanate is bio-based 1,5-pentane diisocyanate; Preferably, the mass percentage content of bio-based carbon in the bio-based 1,5-pentanediisocyanate is 60% to 71.4%; Preferably, the hydrolyzed chlorine content of the bio-based 1,5-pentanediisocyanate is ≤60 mg / kg; Preferably, the solid content of the bio-based 1,5-pentanediisocyanate is 100%.
5. The polyurethane material according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the oligomer polyol is 1000 to 2000; Preferably, the oligomer polyol comprises polyester polyol and / or polyether polyol; Preferably, the polyester polyol includes any one of polybutylene adipate diol, polypropylene sebacate diol or polybutylene sebacate diol or a combination of at least two thereof, and more preferably polybutylene adipate diol; Preferably, the polyether polyol includes polytrimethylene ether glycol and / or polytetramethylene ether glycol, and more preferably polytetramethylene ether glycol.
6. The polyurethane material according to any one of claims 1 to 5, characterized in that: The chain extender includes any one of 1,4-butanediol, 1,3-propylene glycol or 1,6-hexanediol or a combination of at least two thereof, and more preferably 1,4-butanediol and / or 1,3-propylene glycol.
7. The polyurethane material according to any one of claims 1 to 6, characterized in that: The antioxidants include hindered phenol antioxidants and phosphite antioxidants; Preferably, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:(1-2); Preferably, the anti-hydrolysis agent is a monomeric carbodiimide anti-hydrolysis agent; Preferably, the lubricant comprises any one of montan wax, polyethylene wax or special ester wax, or a combination of at least two thereof; Preferably, the catalyst comprises an organotin catalyst.
8. A method for preparing the polyurethane material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing an oligomer polyol, a portion of 1,5-pentanediisocyanate, an antioxidant and an anti-hydrolysis agent, and reacting them to obtain a prepolymer; (2) mixing the prepolymer obtained in step (1), a chain extender and a lubricant, and reacting them to obtain an intermediate product; (3) The intermediate product obtained in step (2), the remaining 1,5-pentanediisocyanate and the catalyst are mixed, heat treated, and aged to obtain the polyurethane material.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the part of 1,5-pentane diisocyanate in step (1) to the remaining 1,5-pentane diisocyanate in step (3) is (0.6-2):1; Preferably, the oligomer polyol in step (1) is obtained by pretreatment at -1 to -0.06 MPa and 105 to 120° C. for 1 to 2 hours by vacuum dehydration; Preferably, the reaction in step (1) comprises reacting at 65-75° C. for 25-35 min, and then reacting at 80-85° C. for another 2-3 h; Preferably, the reaction temperature in step (2) is 70-80°C and the reaction time is 0.5-1.5h; Preferably, the mixing in step (3) is performed under a vacuum condition of -0.06 to -0.08 MPa for 30 to 60 seconds at a stirring speed of 1500 to 2000 rpm; Preferably, the heat treatment in step (3) is performed at a temperature of 115 to 125° C. for 1.5 to 2 hours; Preferably, the aging temperature in step (3) is 95-105° C. and the time is 15-20 hours.
10. Use of the polyurethane material according to any one of claims 1 to 7 in 3D printing.
Citation Information
Patent Citations
3D-printing thermoplastic polyurethane material and preparation method of same
CN105418874A
Low-melting-point polyurethane 3D printing material and preparation method thereof
CN106893306A